DAMPAK TINGGINYA EARLY-AGE MARRIAGE TERHADAP KELAHIRAN PREMATUR DAN BAYI BERAT BADAN LAHIR RENDAH (BBLR) - Asyila Lukman Thalib; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
Nowdays, early marriage is a hot issue and rampant in all parts of the world. In Indonesia, early marriage is not something new. Some people don’t know about the risks involved in early marriage, especially for women. Some risks can occur include premature birth and low birth weight (LBW). Many things can be a factor in babies born prematurely and LBW due to maternal age <20 years, this can be categorized into 2 factors, namely internal factors and external factors. This is where the role of parents in educating their children is very important, early marriage will not occur if parents always supervise social network of their children and use appropriate education patterns. Type of research used by researchers in this article is literature study method. This research carried out with a series of activities to collect library data, read and record and process research materials. This study uses data collection from journals, scientific articles, and previous research thoroughly on the topic of study. The results showed the age factor in pregnancy can affect the risk of preterm birth and low birth weight (LBW), age <20 years is more at risk in experiencing this compared to mothers aged 20-35 years. Early marriage has impact of increasing the risk of preterm birth and LBW in mothers, hence various efforts are made to reduce the level of early marriage. With this study, people's insights will be broadened and efforts will also be made to reduce the number of early marriages in Indonesia.